Design Project Classroom: Fostering Industry-Ready Industrial Designers through Academic-Industry Collaboration - Amirul Fahmi Razali; Addy Putra Md Zulkifli; Sharih Ahmad Mohamad (Wacana Seni Journal of Arts Discourse, 2024)
As the demands of the job market continue to evolve, it becomes imperative for educational institutions to equip students with the necessary skills and competencies to thrive in their respective industries. This article explores the implementation of a design project classroom as an innovative approach to preparing students for the job market, specifically in industrial design. The research employs the method of participant observation combined with interviews to gain valuable insights from industry professionals and student participants. Collaboration with industries is integral to this research, where it enables students to engage directly with real-world design challenges and obtain expert guidance. By leveraging the expertise and resources of these partnerships, this project aims to bridge the gap between academic knowledge and industry expectations. The results of this study showcase several key elements that students need to master before graduating, identified through feedback from both students and mentoring companies. The findings underscore the significance of hands-on experience, interdisciplinary collaboration, and industry engagement in preparing students for successful careers as industrial designers. The positive feedback received from both students and industry partners affirms the effectiveness of this approach in grooming students and enhancing their readiness for the job market. This article contributes to the literature on design education, and the insights provided serve as a foundation for educators and institutions seeking to enhance their design programmes, ensuring that students are adequately equipped with the skills, knowledge, and practical experience to enter the job market.